Factors influencing enterprise resource planning (ERP) adoption and its effect on organizational performance - Kharuddin, Saira (2012)
Enterprise Resource Planning system (ERP) is a highly integrated and coordinated system that enables an organization not only to enhance its operational efficiency but also improve its market responsiveness and innovativeness. However, ERP adoption does not guarantee increase in organizational performance. In response to the increasing needs to identify causes for ERP adoption failure, this study examines factors that influence ERP system adoption decision and effect of ERP adoption on organizational performance. The mediating roles of users’ satisfaction and system usage on the relationship between ERP system adoption and organizational performance are also examined. The economic transaction cost theory and the institutional theory are the underlying theories used to explain factors that impact ERP system adoption.The DeLone and McLean performance model was adopted to analyze the impact of users’ satisfaction and system usage on the relationship between ERP adoption and organizational performance. In conducting this study, data were collected through a questionnaire survey of all companies listed in Bursa Malaysia, as well as 200 companies systematically selected from the Federation of Malaysian Manufacturers (FMM) database. Responses from 136 organizations were analyzed. The results indicate that perceived operational benefits, perceived strategic benefits and mimetic pressure have significant influence on ERP system adoption decision. However, managerial benefits, normative pressure and coercive pressure are not significant in the ERP adoption decision deliberation. As hypothesized, ERP adoption has a significant and positive relationship with organizational performance. The results also show that only system usage mediates the relationship between ERP adoption and organizational performance. The result of this study suggest that careful evaluation and justification processes are appropriately undertaken as evidenced by the significant emphasis on both operational benefits and strategical benefits prior to the adoption of ERP system. The significant effect of mimetic pressure on ERP adoption further indicates that organizations are keen to be at par with their competitors’ technologial capabilities. In addition, organizations also need to promote effective usage of ERP system to ensure improvement in organizational performance could be attained.